The transformation of contemporary health care the market, the laboratory, and the forum - Moreira, Tiago (New York : Routledge, 2012)
"The past three decades have seen enormous changes in the organisation of health care. This book explores the role of knowledge production and technology on these transformations, focusing on the market (attempts to embed principles of economic rationality and efficient use of resources in the shaping and delivery of health care), the laboratory (science, experiments and 'evidence' in the management of research, practice and policy) and the forum (the application of deliberative procedures and other forms of public consultation to health care decision making)"--Provided by publisher.
1. Health care reform and the social sciences : the (not so) great transformation? -- 2. Conceptualising health care change : regimes, implements, boundaries -- 3. The market : a biography of the QALY -- 4. The laboratory : the making of evidence in health care -- 5. The forum : choreographing public deliberation -- 6. The situated complexity of health care -- 7. Conclusion.
Includes bibliographical references (p. [159]-175) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Health care reform; Medical care; Medical policy; Electronic books